Primulina guizhongensis (Gesneriaceae), a new species from Guangxi, China - Zhao, Bo; Pan, Bo; Zhang, Yang; Wen, Fang (Phytotaxa, 2013)
A new species of Primulina is described and illustrated from southern China (Guangxi zhuang Autonomous Region) as P. guizhongensis. This new species is similar to P. spadiciformis based on morphological characters. Sequences of nuclear ribosomal internal transcribed spacer (ITS) region and the plastid trnL-F intronspacer (trnL-F) from the new species and its 22 relatives are used to resolve generic placement of the new species in Primulina. In spite of three species are vastly different in morphology, the molecular evidences showed that the closest relatives of P. guizhongensis are P. mollifolia and P. luochengensis. The conservation threat analysis is summarized according to the IUCN Red List Categories and Criteria.